Simultaneous Observations of SAR Arc and Its Ionospheric Response at Subauroral Conjugate Points (L ≃ 2.5) During the St. Patrick's Day Storm in 2015. Issue 4 (27th March 2020) - Hong, J.; Kim, J.‐H.; Chung, J.‐K.; Kim, Y. H.; Kam, H.; Park, J.; Mendillo, M.
Abstract: During the St. Patrick's Day storm on 17 March 2015, an all‐sky imager at King Sejong Station (KSS; geo: 62.2°S, 58.8°W; mag: 50.2°S) captured diffuse aurora and a stable auroral red (SAR) arc. Ground‐based Global Positioning System observations were also simultaneously conducted at KSS, but there was no significant increase in the total electron content's rate‐of‐change index or the ionospheric scintillation indices around the SAR arc region. Auroral activities including a SAR arc were also detected by the all‐sky imager at Millstone Hill Station (geo: 42.6°N, 71.4°W; mag: 52.5°N), which is magnetically conjugate to KSS. The total electron content's rate‐of‐change index map around Millstone Hill Station, too, indicates that the ionospheric irregularities occurred only near the diffuse aurora and not in the SAR arc. The northern SAR arc is broader than the southern one and also shows a multiplicity pattern, which may be due to latitude structure within the seasonally dependent midlatitude ionospheric trough. These conjugate observations, despite their hemispheric differences, validate the classical SAR arc mechanism of emission driven by heat conduction from the inner magnetosphere that does not generate small‐scale ionospheric irregularities that can affect Global Positioning System radio signals. Previous studies of SAR arcs and very high frequency radiowave scintillations did show a positive correlation. Key Points: A SAR arc and diffuse aurora were simultaneously observed by all‐sky imagers at two conjugate stations during the St. Patrick's Day storm in 2015 Unlike diffuse aurora, SAR arc regions showed no significant increase of ionospheric scintillation indices or the rate of change of the TEC index (ROTI) Our observations at geomagnetic conjugate points suggest that SAR arcs cause no ionospheric irregularities affecting GPS signals, in contrast to effects at VHF